2000
DOI: 10.1046/j.1525-1594.2000.06515.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Induction in Patients Undergoing Regular Online Hemodiafiltration Treatment

Abstract: End-stage renal disease (ESRD) patients are known to suffer from chronic inflammation as the result of an ongoing subacute cytokine induction, which may contribute considerably to dialysis-related, long-term morbidity and mortality. Preparation of infusate from cytokine-inducing dialysis fluid and its administration in large quantities as well as the use of high-flux membranes bear the risk of aggravating the chronic inflammatory response among online hemodiafiltration (online HDF) patients. In order to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Basal and after PMA stimulation production rate of superoxide anion by leukocytes at the beginning and at the end of each session was not significantly different with the 2 modalities. Cytokine induction has also been considered the trigger of the inflammatory response and a critical parameter of dialysis biocompatibility during RRT [37] and high levels of pro-inflammatory cytokines have been associated with increased mortality in AKI [38,39]. We found that both pro-and anti-inflammatory cytokines plasma levels did not increase after HCO HD, suggesting that it might not alter the balance of cytokines production.…”
Section: Discussionmentioning
confidence: 67%
“…Basal and after PMA stimulation production rate of superoxide anion by leukocytes at the beginning and at the end of each session was not significantly different with the 2 modalities. Cytokine induction has also been considered the trigger of the inflammatory response and a critical parameter of dialysis biocompatibility during RRT [37] and high levels of pro-inflammatory cytokines have been associated with increased mortality in AKI [38,39]. We found that both pro-and anti-inflammatory cytokines plasma levels did not increase after HCO HD, suggesting that it might not alter the balance of cytokines production.…”
Section: Discussionmentioning
confidence: 67%
“…However, there is no evidence up to now that pyrogenic reactions occur more frequently during on‐line convective therapies than during low‐flux HD (23,24). Subclinically, no difference between on‐line HDF and conventional HD has been observed, as chronic inflammation was not altered by on‐line HDF and there was no induction of cytokines during the session (25,26).…”
mentioning
confidence: 99%
“…Weber and coworkers could not demonstrate an increase in pro‐inflammatory cytokines or markers of monocyte activation after a 3‐month period of online HDF (11). Others reported a decrease of pro‐inflammatory cytokines (interleukin 6 [IL‐6] and tumor necrosis‐factor α[TNFα]) after switching to online HDF (12) or confirmed the absence of significant leukocyte activation (as measured by TNF‐α and IL‐1 receptor antagonist concentration) in online HDF, with similar results as in low‐flux hemodialysis (13). It is conceivable that different adsorptive properties and biocompatibility of dialysis membranes should be kept in mind when interpreting these results.…”
Section: Role Of Ultrapure Water (Upw)mentioning
confidence: 82%